Chăm sóc bệnh nhân phẫu thuật nội soi tuyến giáp - My, Nguyễn Thị Diệu; Hoa, Châu Thị; Trúc, Nguyễn Thị; Ngân, Nguyễn Thị Ngọc; Bích, Võ Thị Hồng; Hoàng, Nguyễn Thị (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
.